A Liquid Chromatography-Mass Spectrometry Assay for Determination of Perampanel and Concomitant Antiepileptic Drugs in the Plasma of Patients With Epilepsy Compared With a Fluorescent HPLC Assay. Issue 4 (August 2018) - de Grazia, Ugo; D'Urso, Annachiara; Ranzato, Federica; De Riva, Valentina; Contarato, Giorgia; Billo, Giuseppe; Perini, Francesco; Galloni, Elisabetta
Abstract : Background: Perampanel is a novel noncompetitive selective antagonist at the postsynaptic ionotropic alpha-amino-3-hydroxy-5-methyl-4-isoxazoleproprionic acid (AMPA) glutamate receptor, which is approved as an adjunctive agent for the treatment of partial-onset seizure with or without secondary generalization and for primary generalized tonic-clonic seizure in patients with epilepsy who are at least 12 years of age. Limited information is available about the clinical utility of therapeutic drug monitoring of perampanel and therapeutic ranges are so far not established. Therefore, perampanel titration should be performed especially in case of insufficient success of the drug. Methods: The authors developed a selective and sensitive LC-MS/MS (liquid chromatography-mass spectrometry) assay to monitor perampanel concentrations in plasma, which was compared to a commercially available high-performance liquid chromatography kit with fluorescent detection. Perampanel and the internal standard were extracted from plasma samples by a simple protein precipitation. The method allows the simultaneous quantification of perampanel and several other antiepileptic drugs (AEDs). Results: Data were evaluated according to EMA guidelines for bioanalytical method validation. Extraction recovery of perampanel from human plasma was consistently above 98%. No matrix effect was found. Analytical interferences by other AEDs were not observed. The method was linear in the range from 2.5 to 2800 ng/mL. Intra-assay and interassay reproducibility analyses demonstrated accuracy and precision within acceptance criteria. Data collected from 95 patients, given perampanel as their maintenance antiepileptic therapy, showed a very strong correlation between the 2 methods. Conclusions: The assay allows for highly sensitive and selective quantification of perampanel and concomitant AEDs in patient plasma samples and can be easily implemented in clinical settings. Our findings are in agreement with previously published data in patients comedicated with enzyme inducer AEDs, but seem to indicate a possible interaction in patients treated with the enzyme inhibitor drug valproic acid.